Estatuto do idoso: Avanços com contradiç\~oes - Ana Amélia Camarano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This article discusses advances and contradictions of some proposed actions by Elder's Bill of Rights. This Bill was approved in 2003. Its main objective is to regulate the rights of older people in multiple spheres and dimensions. It gathers in a single document many of the bills and policies previously passed. It incorporates new elements, looking to establish measures to provide the welfare of the elderly in the long run. The essence of the Bill is the general rules which provide for the 'full protection' for the elderly. It sets that they should have all the rights inherent to the human beings and that aging is a highly personal right and their protection a social right. The main established rights are: the right to life, protection, health, labor, social security, social assistance, education, culture, leisure, housing and voting.Although the actions proposed mean great advances towards social inclusion of the elderly, it has not been established priorities for their implementation and nor sources for their founding. Therefore, the costs of some of the proposed measures are being shared with the society, which could threaten intergenerational solidarity. It is suggested some changes in the Bill in order to adapt it to demographic and social changes, having as parameter the basic principle of the Madrid Plan. They are: changes in the lower limit of the age that defines elderly population, from 60 to 65 years, the establishment of funding sources for each proposed action, help for families to take care of the dependent elderly, both at home and in the hospital. It also considers the need of the health services to offer actions that can promote a dignified death for those who are suffering from a terminal illness. [...]
Keywords: J14; J18; 330; economics of the elderly; economics of the handicapped; non-labor market discrimination; public policy